Writing a literature review. (September 2016) - Winchester, Catherine L; Salji, Mark
Formal literature reviews are a critical appraisal of a subject and are not only an academic requirement but essential when planning a research project and for placing research findings into context. Understanding the landscape in which you are working will enable you to make a valuable contribution to your field. Writing a literature review requires a range of skills to gather, sort, evaluate and summarise peer-reviewed published data into a relevant and informative unbiased narrative. Digital access to research papers, academic texts, review articles, reference databases and public data sets are all sources of information that are available to enrich your review.